High panel exploitation of Hevea trees: a comparative study of five tapping systems - Zahrin, Ahmad; Wan, C. K. (Universiti Pertanian Malaysia, 1987)
High panel exploitation of Hevea using five different tapping systems was studied. Upward tapping on a quarter-spiral cut for eight months, followed by base panel tapping for four months gave the same yield as downward ladder tapping on a half-spiral cut (control). However, the dry rubber content of the latex was higher; the time taken to tap per tree was {ess; stimulation cost was lower and so was bark consumption. The jebong and CUT knife were compared for upward tapping{ on a quarter-spiral cut and showed no differences on the yield of latex, but it took more time to tap a tree with the jebong knife when the tapping cut reached higher levels. In upward tapping, the yield obtained with the half-spiral cut, was higher than the quarter-spiral cut, but the dry rubber content of the latex was lower. Also, it took a longer time to tap the tree; it had a higher bark consumption and the cost of stimulation was higher compared to the quarter-spiral cut. There was little difference in yield between reverse micro-x and ladder tapping. Reverse micro-tapping gave a higher dry rubber content of the latex .and consumed much less bark, but the stimulation cost was higher, and it took a longer time to tap a tree.